Critical analysis of the performance of women's artistic gymnastics in Brazil in the 2004-2016 Olympic cycles - Inácio Molinari, C.; Ricci Costa, V.; Ferreira Monteiro, K. O. F.; Nunomura, M. (Science of Gymnastics Journal, 2018)
Women`s Artistic Gymnastics (WAG) in Brazil has been represented in the Olympic Games since 1980; however, a full team was classified only in 2004. Analyzing the Brazilian team`s participation over the last four cycles (2004-2016), we have identified several factors that implied in the WAG results. In this study, we discussed these factors and reflected on their contributions to the development of the gymnastics. The milestone of the 2001-2004 Olympic cycle is marked by the first participation of a full team, when foreign coaches came to lead WAG, the training system was reorganized, and the selected athletes began training in a centralized training system in Curitiba`s Training Center. The 2005-2008 Olympic cycle was more successful, as a consequence of the long-term planning. In the 2009-2012 Olympic cycle, the Brazilian WAG went through a period of turbulence, the training was no longer centralized, and the head coach of the Brazilian team returned to his home country. In the 2013-2016 Olympic cycle, with the headquarters of the 2016 Olympic Games in the city of Rio de Janeiro, the Brazilian Olympic Committee devised strategies to boost the country`s success, which again drove improvement in the team results. We concluded that the last Olympic cycles represented a major advance in Brazilian WAG. Restructuring since 2000 has been paramount condition for the gymnastics discipline to reach the current level. The improvement in training and competition conditions, the structuring of a Training Center of excellence, and the multidisciplinary team support was essential for the preparation of Brazilian team in the Olympic Games.